STATE STRATEGIES FOR IMPLEMENTING E-GOVERNMENT AT THE PRESENT STAGE - FiryuzaAbdurashidovna, Mukhitdinova; SvetaBayniyazovna, Amaniyazova (The journal of contemporary issues in business and government, 2021)
The article discusses the main directions of the evolution of e-government. The theoretical aspects of e-government: and the impact of e-government on the effectiveness of the state anti- corruption policy of the country is analyzed. The process of adaptation of e-government by state organizations is identified; the growing crisis of representative democracy is identified, as well as the role of e-government at the present stage in Uzbekistan and the legal basis for modernization.